2017
DOI: 10.1007/s00338-017-1553-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperate macroalgae impacts tropical fish recruitment at forefronts of range expansion

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Abstract Warming waters and changing ocean currents are increasing the supply of tropical fish larvae to temperature regions where they are exposed to novel habitats, namely temperate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…To our knowledge, rabbitfish are the only group of tropical herbivores documented as reproductively active at high latitudes [61]. Siganus fuscescens can recruit to kelp forests [62], indicating that temperate reefs are suitable for juveniles. Nevertheless, thermal tolerance is narrower in juvenile stages and extreme low temperatures can cause high rates of mortality [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, rabbitfish are the only group of tropical herbivores documented as reproductively active at high latitudes [61]. Siganus fuscescens can recruit to kelp forests [62], indicating that temperate reefs are suitable for juveniles. Nevertheless, thermal tolerance is narrower in juvenile stages and extreme low temperatures can cause high rates of mortality [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to corals, kelps and other habitat‐forming seaweeds, turf algae provide minimal structure and habitat functions (Filbee‐Dexter & Wernberg, ). Nevertheless, some structurally simple habitats, including turf algae dominated habitats, can be functionally important as juvenile fish nurseries for some species (Galaiduk, Figueira, Kingsford, & Curley, ), including many range‐shifting tropical species (Beck, Feary, Nakamura, & Booth, ). This suggests that the replacement of kelp forests by turf algae may create a positive feedback loop that facilitates tropicalisation of temperate reefs, especially in areas where boulders may also offer abiotic refuge spaces.…”
Section: Predicted Impacts To Biodiversity Ecosystem Functions and Sermentioning
confidence: 99%
“…In contrast to corals, kelps and other habitat-forming seaweeds, turf algae provide minimal structure and habitat functions (Filbee-Dexter & . Nevertheless, some structurally simple habitats, including turf algae dominated habitats, can be functionally important as juvenile fish nurseries for some species (Galaiduk, Figueira, Kingsford, & Curley, 2013), including many range-shifting tropical species (Beck, Feary, Nakamura, & Booth, 2017…”
Section: Provision Of Habitat and Nursery Functions And Implicationmentioning
confidence: 99%
“…High seawater temperatures may decrease winter mortality of K. bigibbus, leading to an increase in the number of overwintering individuals that are able to spawn the following season (Figueira and Booth 2010). Beck et al (2017) indicated that temperate macroalgal patches may strongly inhibit the recruitment of many tropical reef fish species, primarily planktivores and herbivores. The noticeable losses of kelp forests in 1998 may have facilitated the rapid increase in K. bigibbus recruitment since 1999.…”
Section: Discussionmentioning
confidence: 99%